2020
DOI: 10.3389/fpsyt.2020.561685
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Disorder With Panic Attacks After Replacement of an Intrauterine Device Containing Levonorgestrel: A Case Report

Abstract: The levonorgestrel-releasing intrauterine system (LNG-IUS) is used as hormonal contraception by millions of women worldwide. It is considered as a safe device with low rates of systemic adverse drug reactions (ADRs). However, an emerging evidence suggest mood changes as ADRs. Whereas most of these studies report psychiatric ADRs after the first implantation of the LNG-IUS, it has to be considered that these may also occur after replacement, even when psychiatric symptoms were not evident at the time of the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The results showed a positive association between the prescription of an LNG-IUS and depression and a nonsignificant association of LNG-IUSs with anxiety and sleep problems in women without these conditions before the use of the IUD. In addition, Zeiss et al ( 22 ) reported a case of a 41-year-old woman who developed depressive and anxiety symptoms after her second LNG-IUS. After a complete examination, a mental disorder was considered.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed a positive association between the prescription of an LNG-IUS and depression and a nonsignificant association of LNG-IUSs with anxiety and sleep problems in women without these conditions before the use of the IUD. In addition, Zeiss et al ( 22 ) reported a case of a 41-year-old woman who developed depressive and anxiety symptoms after her second LNG-IUS. After a complete examination, a mental disorder was considered.…”
Section: Discussionmentioning
confidence: 99%